2020
DOI: 10.3390/ijerph17134660
|View full text |Cite
|
Sign up to set email alerts
|

How Do Hospital Medical and Nursing Managers Perceive Work-Related Strain on Their Employees?

Abstract: Health-oriented supportive leadership behavior is a key factor in reducing work stress and promoting health. Employees in the health sector are subject to a heavy workload, and it has been shown that 40% of them show permanent health problems. A supportive leadership behavior requires the manager’s awareness of the employees’ well-being. However, little is yet known about how medical and nursing managers perceive the well-being of their staff. To explore this issue, we conducted a total of 37 semi-standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…The toxic leadership style is one of the main threats to the mental well-being of individuals in the working environment (Mergen and Ozbilgin, 2021;Worringer et al, 2020). Vincent-H€ oper et al (2017) reported that one of the problematic aspects of working life was working with dysfunctional and toxic leaders.…”
Section: Toxic Leadership and Mental Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxic leadership style is one of the main threats to the mental well-being of individuals in the working environment (Mergen and Ozbilgin, 2021;Worringer et al, 2020). Vincent-H€ oper et al (2017) reported that one of the problematic aspects of working life was working with dysfunctional and toxic leaders.…”
Section: Toxic Leadership and Mental Well-beingmentioning
confidence: 99%
“…The toxic leadership style is one of the main threats to the mental well-being of individuals in the working environment (Mergen and Ozbilgin, 2021; Worringer et al. , 2020).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…In addition, studies have shown that work-related strain had an adverse impact on nurses' physical and mental health, thereby reducing their level of motivation, job performance, and job satisfaction [12] as well as the quality of patient care and safety [13], leading to high turnover rates. Work-related strain was also found to adversely affect team climate, social support, and coping negativity that could be related to social intelligence [14].…”
Section: Introductionmentioning
confidence: 97%
“…As a result, nurses have experienced moral and emotional distress [ 9 , 10 ], including feelings of grief, anger, frustration, compromised moral integrity, and diminished self-esteem [ 11 , 12 , 13 ]. Professionally, they have encountered difficulties in interpersonal communication, lack of leadership, and desire to leave the profession [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%